2007
DOI: 10.1007/s10562-007-9221-7
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Degradation of Nitrobenzene and Aniline in Presence of Ozone by Magnesia from Natural Mineral

Abstract: In this work, magnesia from natural brucite mineral has been used firstly for catalytic degradation of nitrobenzene and aniline in presence of ozone. Compared with single ozonation, the catalytic ozonation accelerated markedly the degradation of nitrobenzene and aniline. The influences of hydroxyl radical scavengers, pH values, and reaction temperatures on degradation were investigated. It was found that the essential of catalysis was the homogeneous catalysis of hydroxyl ions in water, which accelerated the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…Many researchers indicate that pH is an important influencing factor in the advanced oxidation process (Agustina, Ang, & Vareek, 2005;Borghei & Hosseini, 2008;Dong, He, Yin, & Zhang, 2007;Mok, Jo, & Lee, 2008;Tong, Xie, Wei, & Liu, 2005). Our studies in water were consistent with them.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers indicate that pH is an important influencing factor in the advanced oxidation process (Agustina, Ang, & Vareek, 2005;Borghei & Hosseini, 2008;Dong, He, Yin, & Zhang, 2007;Mok, Jo, & Lee, 2008;Tong, Xie, Wei, & Liu, 2005). Our studies in water were consistent with them.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, heterogeneous catalytic ozonation was intensively explored in the degradation of various dyes, including methyl orange [Tizaoui et al, 2015], active brilliant red X-3B [Dong et al, 2007], reactive blue 5 [Yong et al, 2005]. In most cases, metal oxide (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ikhlaq supposed that highest activity of zeolite was at pH close to the point of zero charge where surface hydroxyl radicals are most susceptible to conversion of ozone to hydroxyl radicals [Ikhlaq et al, 2012]. Other natural minerals as effective ozonation catalysts include brucite , Qi et al, 2009, magnesia [Dong et al, 2007], volcanic sand [Vald es et al, 2008]. However, relatively limited catalytic activity weakened the potential of natural minerals as the cost-efficient catalysts [Vald es et al, 2008;Moussavi et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…As we know these metal ions would lead to a secondary pollution in water. Heterogeneous catalytic ozonation also has been studied a lot, catalysts proposed in this process are metal oxides, metals or metal oxides on supports (metal oxides, activated carbon and zeolite) [3][4][5][6][7][8][9][10][11], and several studies have been performed to present the mechanism of heterogeneous catalytic ozonation [11][12][13][14], Andreozzi et al [12] have studied the mechanism of decomposition of oxalic acid with manganese dioxide ozonation, and have revealed that the catalytic effect should be mainly attributed to ozone adsorption and a series of reactions on catalyst surface. Beltrán et al [13] concluded that surface reactions between ozone and hydrogen peroxide on the activated carbon, which generated free radicals, played an important role on organic compound removal.…”
Section: Introductionmentioning
confidence: 99%